If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5t + 4 = 1t + -2 Reorder the terms: 4 + 5t = 1t + -2 Reorder the terms: 4 + 5t = -2 + 1t Solving 4 + 5t = -2 + 1t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-1t' to each side of the equation. 4 + 5t + -1t = -2 + 1t + -1t Combine like terms: 5t + -1t = 4t 4 + 4t = -2 + 1t + -1t Combine like terms: 1t + -1t = 0 4 + 4t = -2 + 0 4 + 4t = -2 Add '-4' to each side of the equation. 4 + -4 + 4t = -2 + -4 Combine like terms: 4 + -4 = 0 0 + 4t = -2 + -4 4t = -2 + -4 Combine like terms: -2 + -4 = -6 4t = -6 Divide each side by '4'. t = -1.5 Simplifying t = -1.5
| J(8j-7)=0 | | -3x+-6= | | 6(2a+10)=5a+5 | | 21-2x=43-5x | | 6d-2= | | (x)/(2)-1=2-x | | ×/3=11 | | (-4.3)-z=11 | | 2x+2=4+6x-54 | | 47-7x=5x-20 | | (S+5)(8s+9)=0 | | 7.9x-17.9=29.5 | | -12(x+4)=-3(x+6)+x-30 | | 0.5(4x-1)=4(3+x) | | 2a+28=4a-4 | | 144-5x=171-8x | | 3(x+3)-10=32 | | 6x+5+3x=136 | | 12-x=36 | | (7n-3)(6n-7)=0 | | h=(-16)t^2+800(t)+125 | | sin(5t)-cos(5t)=0 | | 6a-5= | | (8z-1)(z+3)=0 | | 130x+46=7 | | H(2h+9)=0 | | 4(6+4n)=120 | | y=2x^2+19y-10 | | 3.4x-2.3(x-1)=6.6 | | (6y-5)(4y+7)=0 | | 18m-31=59 | | 6x+6+6x-2+2-2x=6x+12+x+15 |